ART treatment costs and retention in care in Kenya: a cohort study in three rural outpatient clinics. Issue 1 (2nd January 2013) - Larson, Bruce A; Bii, Margaret; Henly‐Thomas, Sarah; McCoy, Kelly; Sawe, Fredrick; Shaffer, Douglas; Rosen, Sydney
Abstract : Introduction: After almost 10 years of PEPFAR funding for antiretroviral therapy (ART) treatment programmes in Kenya, little is known about the cost of care provided to HIV‐positive patients receiving ART. With some 430, 000 ART patients, understanding and managing costs is essential to treatment programme sustainability. Methods: Using patient‐level data from medical records ( n= 120/site), we estimated the cost of providing ART at three treatment sites in the Rift Valley Province of Kenya (a clinic at a government hospital, a hospital run by a large agricultural company and a mission hospital). Costs included ARV and non‐ARV drugs, laboratory tests, salaries to personnel providing patient care, and infrastructure and other fixed costs. We report the average cost per patient during the first 12 months after ART initiation, stratified by site, and the average cost per patient achieving the primary outcome, retention in care 12 months after treatment initiation. Results: The cost per patient initiated on ART was $206, $252 and $213 at Sites 1, 2 and 3, respectively. The proportion of patients remaining in care at 12 months was similar across all sites (0.82, 0.80 and 0.84). Average costs for the subset of patients who remained in care at 12 months was also similar (Site 1, $229; Site 2, $287; Site 3, $237). Patients not retained in care cost substantially less (Site 1, $104; Site 2, $113; Site 3, $88). For the subset of patients who remained in care at 12 months, ART medications accounted for 51%, 44% and 50% of the costs, with the remaining costs split between non‐ART medications (15%, 11%, 10%), laboratory tests (14%, 15%, 15%), salaries to personnel providing patient care (9%, 11%, 12%) and fixed costs (11%, 18%, 13%). Conclusions: At all three sites, 12‐month retention in care compared favourably to retention rates reported in the literature from other low‐income African countries. The cost of providing treatment was very low, averaging $224 in the first year, less than $20/month. The cost of antiretroviral medications, roughly $120 per year, accounted for approximately half of the total costs per patient retained in care after 12 months.